2012
DOI: 10.1097/sle.0b013e318247bb84
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Novel 3-Step Protocol for Biliary Cannulation—A Prospective Analysis

Abstract: Traditionally, a 2-step protocol has been used for deep biliary cannulation. The purpose of the present prospective study was to find out the feasibility and safety of the novel sequential 3-step protocol (traditional cannula with guidewire, double-guidewire, and needle-knife techniques) for deep biliary cannulation. All consecutive patients admitted for endoscopic retrograde cholangiopancreatography (ERCP) to a single, very experienced ERCP endoscopist during the year 2009 with intended biliary cannulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The literature predominantly reports outcomes from academic centres, where case mix and experience may differ from other settings. The included studies reported cannulation rates from 70.5 to 100%, 1743 with a median of 96% and mean of 91.4%. The consensus of the working party was that a competent ERCP practitioner should achieve a cannulation rate in excess of 90% with a target standard of 95% at expert centres.…”
Section: Domain: Completeness Of Proceduresmentioning
confidence: 99%
“…The literature predominantly reports outcomes from academic centres, where case mix and experience may differ from other settings. The included studies reported cannulation rates from 70.5 to 100%, 1743 with a median of 96% and mean of 91.4%. The consensus of the working party was that a competent ERCP practitioner should achieve a cannulation rate in excess of 90% with a target standard of 95% at expert centres.…”
Section: Domain: Completeness Of Proceduresmentioning
confidence: 99%